2021
DOI: 10.4093/dmj.2020.0175
|View full text |Cite|
|
Sign up to set email alerts
|

Trends in Cardiovascular Complications and Mortality among Patients with Diabetes in South Korea

Abstract: We investigated the cardiovascular complications and mortality rates of patients with diabetes in South Korea. The rates of hospitalization due to cardiovascular complications and mortality were analyzed using the Korean National Health Insurance Service-National Sample Cohort. From 2006 to 2015, the rates of hospitalization due to major cardiovascular complications decreased, while those due to heart failure (from 72 to 146 and 124 to 161 per 10,000 men and women, respectively) and peripheral artery disease (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 19 publications
2
35
0
Order By: Relevance
“…The increasing prevalence of obesity has led to significant increases in the prevalence and incidence of T2DM [14]. However, among patients with diabetes, there has been a contrasting decrease in the incidence of CVD or CV death within the last two decades [6,[15][16][17][18][19][20][21]. Analysis of the Swedish nationwide registry data from 1998 to 2014 showed that there was a marked reduction of 20% in hospitalization for CVD and CV mortality among patients with T2DM [16].…”
Section: Epidemiology Of Cvdmentioning
confidence: 99%
See 2 more Smart Citations
“…The increasing prevalence of obesity has led to significant increases in the prevalence and incidence of T2DM [14]. However, among patients with diabetes, there has been a contrasting decrease in the incidence of CVD or CV death within the last two decades [6,[15][16][17][18][19][20][21]. Analysis of the Swedish nationwide registry data from 1998 to 2014 showed that there was a marked reduction of 20% in hospitalization for CVD and CV mortality among patients with T2DM [16].…”
Section: Epidemiology Of Cvdmentioning
confidence: 99%
“…These trends of CVD prevalence in diabetes are consistent with those reported by Asian studies. Analyses using data from the National Health Insurance Service database of Korea indicated that the incidence of CVD in T2DM has been decreasing annually [20,21]. Although the overall incidence rate of CVD shows decreasing trends, there has been some evidence of a paradoxical increase in heart failure (HF) in adults with diabetes [21,22].…”
Section: Epidemiology Of Cvdmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase of prevalence rate may be due to a decrease in mortality in the elderly. We have shown that mortality is decreasing in people with diabetes in the period 2007 to 2015 [15]. Another explanation is that national and individual activities including education and campaigns to prevent diabetes for people at high-risk of diabetes might have led to decrease of diabetes incidence [16,17].…”
Section: Discussionmentioning
confidence: 86%
“…The incidence of CV events and deaths has been decreasing over the past two decades [11][12][13]. However, the healthcare expenditure for CV disease is higher (12-16.5%) than that for other diseases (0.2-0.4%) [14].…”
Section: Discussionmentioning
confidence: 99%